Community voices from modern maternal waiting home users in Zambia - Mwansa, Melvin Kunda; Chimpinde, Kafiswe; Naidoo, Mergan (Frontiers in Global Women's Health, 2024)
Objective This study aimed to understand community voices on factors influencing utilisation of MMWHs in Zambia. Methods The study employed a mixed method study design in four selected health facilities across Zambia districts between January 2021 and December 2022. Purposeful sampling was used to select study participants using MMWH registers as the sampling frame for mothers who had utilised MMWHs and their spouses. Sampling of participants through face-to-face, in-depth interviews (IDIs) and focus group discussions (FGDs) was conducted to saturation in all targeted health facilities Data was transcribed verbatim and analysed thematically. Results Results found that the comfortable state of the MMWHs, long distances to health facilities, fear of maternal complications, availability and positive attitudes of specialized health personnel, and the information on childcare provided were major factors. Spouses supported their partners using MMWHs due to the quality of care and the availability of modern equipment and furniture. However, some spouses indicated that utilisation of MMWHs has a bearing on a household's financial resources. Conclusion MMWHs are a pivotal intervention in improving maternal outcomes. All health facilities had no maternal and newborn complications or deaths over the study period.